Multi-period supply and demand balance of large-scale and complex natural gas pipeline network: Economy and environment. (1st February 2023) - Wen, Kai; Qiao, Dan; Nie, Chaofei; Lu, Yangfan; Wen, Feng; Zhang, Jing; Miao, Qing; Gong, Jing; Li, Cuicui; Hong, Bingyuan
Abstract: The "dual carbon goal" and "one country network" indicate the greater challenge of balancing supply and demand in natural gas pipeline networks. This paper proposes an optimization method for supply and demand balance of large and complex natural gas pipeline network to respond the demand changes of downstream users by making the peak shaving and flow rate allocation scheme, considering carbon emission targets to improve economic and environmental benefits. This method considers the pipeline network elements including bidirectional pipeline, multiple pipeline structure, compressor station and gas storage so on, and couples the hydraulic characteristics to accurately describe the hydraulic situation of the pipeline under each allocation scheme. Case 1 shows that the economic efficiency is optimized by 15.58% and compensates for the overgrowth demand generated through the initial stage. Compared with TGNET, the average relative error of hydraulic was only 2.89%. Case 2 shows that the optimal flow rate allocation scheme can be further improved in the case of multiple pipelines. Case 3 for a large-scale pipeline network reduces 58% annual carbon emissions by adjusting the flow rate allocation scheme. This study can provide decision support for the allocation and operation of natural gas pipeline network. Highlights: A method is proposed to describe the complex natural gas pipeline network system. A multi-period optimization model of supply and demand balance is proposed. Economic and environmental benefits are taking as objective function. The peak shaving and the hydraulic characteristics are considered.